(untitled) - Monteith, John Lennox (London, 1990)
Environmental Physics concerns the description and analysis of physical processes that establish the conditions in which all species of life survive and reproduce. The subject involves a synthesis of mathematical relations that describe the physical nature of the environment and the many biological responses that environments evoke. Environmental Physics provides a basis for understanding the complex responses of plants and animals to environmental change. International concern with climate change has made both politicans and the general public much more aware of the impact of local and global weather on all aspects of domestic life, industry and commerce. Environmental Physics has become more widely used by biologists, atmospheric scientists and climate modellers to specify interations between surfaces and the atmosphere. This new edition contains further material on causes of global warming, applications of remote sensing, and the carbon and water cycles of crops and forests. * Presents a unique synthesis of micrometeorology and ecology in its widest sense. * Deals quantitatively with the impact of weather on living systems but also with the interactions between them that are a central feature of life on earth * Includes an up-to-date bibliography and review of recent micrometeorological applications in forestry, ecology, hydrology and agriculture * Includes numerical problems and worked examples
Keywords: Ecology.,Biophysics,Khoa lý sinh học; Sinh thái học